Il romanzo filosofico tedesco intorno al 1800. Appunti per una teoria - Campana, Francesco (Itinerari, 2024)
This paper aims to investigate the status of the philosophical novel specifically through its development in the context of Germany around 1800. Consequently, I analyze the writings of authors from the period (e.g., Friedrich Schlegel, Friedrich Hölderlin, and Friedrich Heinrich Jacobi), focusing on programmatic and theoretical texts to extract elements to establish a theory of the philosophical novel. Accordingly, after a brief introduction to the contemporary debate over what a philosophical novel is, I emphasize the centrality of the genre in German aesthetics around 1800, reflecting on passages taken from novels of the period that can be considered philosophical (e.g., Hyperion, Allwill, and Woldemar). Ultimately, what emerges as a distinctive feature of the philosophical novel for these authors is the fact that it contains, in a paradoxically constitutive way, philosophy and literature as two distinct but simultaneously inseparable dimensions.